Sistem Informasi Administrasi Pengelolaan Dana Masjid Berbasis Web menggunakan Codeigniter pada Masjid Jami’ Nurul Islam - Kasruddin, Muhammad Ikhsan; Sugiharto, Riki; Sugara, Victor Ilyas (Sekolah Tinggi Ilmu Komputer El Rahma, 2023)
This research aims to develop a web-based Mosque Fund Administration Information System using the CodeIgniter framework. The system's objective is to assist mosque administrators in managing and monitoring mosque funds more effectively and efficiently. The software development method employed is Rapid Application Development (RAD), with Unified Modeling Language (UML) serving as the system documentation model. Software testing is conducted through black-box testing. Data for this research is collected through observation techniques, interviews, and literature studies. The research results indicate that the developed Web-Based Mosque Fund Administration Information System has the potential to assist mosque administrators in managing and monitoring mosque fund administration more effectively and efficiently.